2015
DOI: 10.1007/s11055-015-0117-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Rehabilitation: Importance of Neuroplasticity and Sensorimotor Integration Processes

Abstract: Stroke remains one of the leading causes of disability and social maladaptation of patients, residual signs of stroke of different severities being seen in 65% of patients [1,2]. Data from the National Stroke Register provide evidence that only about 20% of patients surviving stroke are able to return to their former work [3]. Correctly planned rehabilitation measures are very important for this group of patients, these being effective to some extent or other in 80% of stroke patients, with spontaneous complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…While it has been suggested that brain recovery occurring spontaneously may plateau at six months post-stroke (Nudo, 1999), these results indicate that motor imagery treatment may be effective sometime after this. The precise mechanisms underpinning neural plasticity and recovery of function are subject to continuing research and debate (Ekusheva & Damulin, 2015;Nudo, 2007) and we suggest that the development of guidelines on the best time to implement motor imagery will need to take place in tandem with this.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been suggested that brain recovery occurring spontaneously may plateau at six months post-stroke (Nudo, 1999), these results indicate that motor imagery treatment may be effective sometime after this. The precise mechanisms underpinning neural plasticity and recovery of function are subject to continuing research and debate (Ekusheva & Damulin, 2015;Nudo, 2007) and we suggest that the development of guidelines on the best time to implement motor imagery will need to take place in tandem with this.…”
Section: Discussionmentioning
confidence: 99%
“…В раннем постнатальном периоде индуктором апоптоза является ограничение притока афферентной информации, которая служит источником трофических стимулов как для развивающейся, так и для уже зрелой нервной системы. Это подтверждается тем фактом, чтоприток сенсорной информации является организатором процессов созревания и трофического обеспечения нервной системы [46,47,48]. То есть, непрерывный приток информации выступает в качестве главного условия существования и развития нервной системы.…”
Section: функциональная анатомия нервной системы и нейрогенезunclassified
“…It has become a popular practice for health maintenance and illness recovery in the global community [27] and is the way of life and cultural heritage in Nepal [28]. Yoga has many physical exercises with highly positive signi cant effect on stroke rehabilitation [29,30], through enhancing neuroplasticity and neural pathways [31] that could enhance functional ability [32]. In addition, it also incorporates physical, mental and spiritual elements which have the power to integrate and balance among body, mind and spirit of an individual's health in various illnesses [33,34] that enhanced motivation, positive attitude, and activity participation [35,32] and high adherence to the program [36] which were lacking in conventional rehabilitation therapies [37].…”
Section: Introductionmentioning
confidence: 99%